Defect minimization and morphology optimization in TiO2 nanotube thin films, grown on transparent conducting substrate, for dye synthesized solar cell application - Kuzmych, Oleksandr (2013)
TiO2 nanotube (TNT) arrays have proven to be a perspective material for dye- or semiconductor sensitized solar cells. Although their preparation by anodic oxidation method is well elaborated for Ti foil substrate, the synthesis of high quality, homogeneous TNT arrays on a transparent conductive oxide (TCO) is still associated with some experimental challenges. In this paper we present a way of preparation of defect-free, homogenous TNT film on a TCO substrate by a combination of high temperature Ti sputtering and controlled “interrupted” anodization in viscous electrolyte. High temperature of the substrate during Ti sputter coating was found crucial for good adhesion between the Ti thin film and TCO, which seems to be the most important condition for synthesis of TNTs from a Ti thin film. The reason of poor adhesion of the Ti layer sputtered at room temperature is discussed in terms of internal stress forces. An Ar-ion sputtering was proposed as a method for removal of the non-organized top porous layer to reveal a well organized tubular geometry of TNTs and control their final lengths. Such control of morphology of the top layer is important for preparation of solid state solar cells.